International Remittances – A proposal how to test hypotheses about determinants of remittances with macroeconomic time series - Peter Karpestam; Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2011)
We study the determinants of remittances to developing countries at different time horizons. Remittances to developing countries nowadays exceed official development assistance and constitute a significant fraction of the disposable income of many households in developing countries. Different hypotheses suggest that remittances are often sent to compensate for low incomes, which may impose a downward bias when estimating their effects on the economic development (e.g. growth, poverty and consumption) in recipient countries. Two popular hypotheses about the causes of remittances are the altruism and insurance hypothesis. Both hypotheses suggest that remittances are sent to compensate for short-run economic declines, but the altruism hypotheses also predict that remittances should diminish gradually over time as the economic development in the receiving countries proceeds and the need for outside assistance decreases. Hence, the altruism hypothesis predicts a negative correlation between the economic conditions in the receiving countries and remittances in the long-run and the short-run, while the insurance hypothesis only predicts a negative relationship in the short run. We can thus test which hypothesis that is best supported the data by studying the correlation between remittances and consumption in receiving countries at different time horizons. For this purpose we use a macroeconomic panel with consumption and remittances data from 50 low and middle income economies between 1980 and 2006. We estimate Keynesian consumption functions with GDP and remittances per capita as explanatory variables for the full panel and for different subpanels. The data is decomposed into different time horizons using a maximal overlap discrete wavelet transform. We are not aware of any study which uses similar econometric techniques to test different hypotheses about the underlying causes of remittances. Our evidence predominantly supports a negative long-run relationship, which favours the altruism over the insurance hypothesis.
Keywords: C23; C33; E27; F24; 330; Remittances; Altruism; Insurance Hypothesis